2021
DOI: 10.1002/cne.25277
|View full text |Cite
|
Sign up to set email alerts
|

AAV‐BR1 targets endothelial cells in the retina to reveal their morphological diversity and to deliver Cx43

Abstract: Endothelial cells (ECs) are key players in the development and maintenance of the vascular tree, the establishment of the blood-brain barrier and control of blood flow. Disruption in ECs is an early and active component of vascular pathogenesis. However, our ability to selectively target ECs in the CNS for identification and manipulation is limited. Here, in the mouse retina, a tractable model of the CNS, we utilized a recently developed AAV-BR1 system to identify distinct classes of ECs along the vascular tre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…Then we wanted to examine the distribution and potential of the AAV-BR1 vector in healthy BALB/c mice, as this viral vector, to our knowledge, never have been investigated in this specific inbred mouse strain. Previous studies with the AAV-BR1 vector have included FVB/N and C57BL/6 mice (Carroll et al;2020;Chen et al, 2020;Dogbevia et al, 2017Dogbevia et al, , 2020Ivanova et al, 2021;Körbelin et al, 2016;Park et al, 2021;Sundaram et al, 2021). For that purpose, two different constructs were designed and used to study the in vivo distribution of the AAV-BR1 vector.…”
Section: Viral Distribution In Vivo Following Intravenous Injectionmentioning
confidence: 99%
“…Then we wanted to examine the distribution and potential of the AAV-BR1 vector in healthy BALB/c mice, as this viral vector, to our knowledge, never have been investigated in this specific inbred mouse strain. Previous studies with the AAV-BR1 vector have included FVB/N and C57BL/6 mice (Carroll et al;2020;Chen et al, 2020;Dogbevia et al, 2017Dogbevia et al, , 2020Ivanova et al, 2021;Körbelin et al, 2016;Park et al, 2021;Sundaram et al, 2021). For that purpose, two different constructs were designed and used to study the in vivo distribution of the AAV-BR1 vector.…”
Section: Viral Distribution In Vivo Following Intravenous Injectionmentioning
confidence: 99%
“…We found that a single dose of AAVBR1.GFP (5 × 10 8 vg), representing the low–moderate range of subretinal dosage in mice, was sufficient to disperse capsid beyond the subretinal bleb to all retinal quadrants. The AAVBR1 capsid differs from AAV2 by only seven consecutive amino acids in its peptide-binding motif, conferring a considerable shift in its tropism profile [ 6 , 7 ]. The high affinity of AAV2 for heparan sulfate proteoglycans [ 11 ] ensures that AAV2 will rapidly bind wherever it lands within the heparin-rich subretinal landscape, vastly limiting its viral distribution following subretinal delivery.…”
Section: Discussionmentioning
confidence: 99%
“…The recently engineered AAVBR1 is a capsid differing from AAV2 by seven consecutive amino acids in its binding motif. Developed via artificial selection in mice to target CNS microvascular endothelium, the systemic delivery of AAVBR1 shows excellent specificity and expression in mouse brain vasculature at a moderate dose of 5 × 10 10 vg in 100 L [ 6 ], while systemic injection of 1 × 10 11 vg in 100 L showed excellent signal in retinal microvasculature [ 7 ]. While examining its retinal tropism, we fortuitously found that the moderate dosage of AAVBR1 (5 × 10 8 vg) showed exceptional lateral spread following subretinal injection, with strong tropism for both RPE and the outer retina.…”
Section: Introductionmentioning
confidence: 99%
“…The Cx43 GJ decoupling inhibitor danegaptide improves GJIC in retinal vessels under high glucose conditions and reduces cell apoptosis ( Kim et al, 2018 ). Furthermore, establishing an inducible specific ectopic Cx43 expression system in endothelial cells can compensate for the reduction of endogenous Cx43, providing a potentially powerful tool for treating diabetic microcirculatory defects ( Ivanova et al, 2022 ). These studies collectively suggest that DM damages Cx43 and its mediated GJIC, providing further research directions for improving this imbalance.…”
Section: Hyperglycemic and Nvc Impairmentmentioning
confidence: 99%